Foreign Language Classroom Anxiety of Arab learners of English: The effect of personality, linguistic and sociobiographical variables - Dewaele, Jean-Marc; Al-Saraj, Taghreed M. (Studies in Second Language Learning and Teaching, 2015)
The present study focuses on the link between psychological, sociobiographical and linguistic variables and Foreign Language Classroom Anxiety of 348 Arabic learners of English (250 females, 98 males). Data were collected using the Arabic Foreign Language Anxiety Questionnaire (AFLAQ; Al-Saraj, 2011, 2014) and an Arabic version of the Multicultural Personality Questionnaire-Short Form (MPQ-SF; van der Zee, van Oudenhoven, Ponterotto & Fietzer, 2013). Multiple regression analyses revealed that self-perceived proficiency in oral English and frequency of use of English explained over a third of variance in FLCA: More proficient and frequent users felt less anxious. Two personality traits, Emotional Stability and Social Initiative explained a further fifth of variance in FLCA, with emotionally stable and more extraverted participants scoring lower on FLCA. Age was the final predictor of a small amount of variance, with older participants feeling less anxious. Degree of multilingualism, sex and education level had no effect on FLCA.